PSYCHOLOGICAL PECULIARITIES OF THE FORMATION OF ALTRUISTIC MOTIVES IN UNORGANIZED YOUTH - Atabaeva Nargis Batirovna (The American Journal of Social Science and Education Innovations, 2024)
In this article, the concept of unorganized youth, its psychological interpretation, and the possibility of increasing their social awareness by forming altruistic motives in unorganized youth are analyzed.